Affine periodic solutions for some stochastic differential equations - Ruichao Guo; Hongren Wang (Boundary Value Problems, 2023)
Abstract In this paper, we are study the problem of affine periodicity of solutions in distribution for some nonlinear stochastic differential equation with exponentially stable. We prove the existence and uniqueness of stochastic affine periodic solutions in distribution via the Banach fixed-point theorem.